Use of synchrotron-based radiography to diagnose pulsed power driven wire explosion experiments - Theocharous,SP; Bland,SN; Yanuka,D; Rososhek,A; Olbinado,MP; Rack,A; Krasik,YE (Review of Scientific Instruments, 2019)
We describe the first use of synchrotron radiation to probe pulsed power driven high energy density physics experiments. Multi-frame x-ray radiography with interframe spacing of 704 ns and temporal resolution of <100 ps was used to diagnose the electrical explosion of different wire configurations in water including single copper and tungsten wires, parallel copper wire pairs, and copper x-pinches. Such experiments are of great interest to a variety of areas including equation of state studies and high pressure materials research, but the optical diagnostics that are usually employed in these experiments are unable to probe the areas behind the shock wave generated in the water, as well as the internal structure of the exploding material. The x-ray radiography presented here, performed at beamline ID19 at European Synchrotron Radiation Facility (ESRF), was able to image both sides of the shock to a resolution of up to 8 μm, and phase contrast imaging allowed fine details of the wire structure during the current driven explosion and the shock waves to be clearly observed. These results demonstrate the feasibility of pulsed power operated in conjunction with synchrotron facilities, as well as an effective technique in the study of shock waves and wire explosion dynamics.